Deficiency of the 15-kDa selenoprotein led to cytoskeleton remodeling and non-apoptotic membrane blebbing through a RhoA/ROCK pathway - Bang, Jeyoung (Biochem Biophys Res Commun, 2014)
The 15-kDa selenoprotein (Sep15) has been implicated in etiology of some types of cancer. Herein, inducible RNAi cell lines were established and cell morphology and motility were analyzed. The majority of Sep15-deficient cells (>95%) formed membrane blebs in a dynamic manner. Blebbing cells transformed cell morphology from a normal flat spindle shape to a spherical morphology. In blebbing cells, actin fibers moved to the cell periphery, covering and obscuring visualization of α-tubulin. Bleb formation was suppressed by the inhibitors of Rho-associated protein kinase (ROCK), RhoA or myosin light chain (MLC), restoring blebbing cells to wild-type morphology. RhoA activation and phosphorylation of myosin phosphatase target subunit 1 was induced by Sep15 knockdown. Sep15-deficient cells were non-apoptotic, and displayed a distinct relative localization of F-actin and α-tubulin from typical apoptotic blebbing cells. Our data suggest that Sep15 in Chang Liver cells regulates the pathway that antagonizes RhoA/ROCK/MLC-dependent non-apoptotic bleb formation.